The link between healthcare risk identification and patient safety culture - Simsekler, Mecit Can Emre (International journal of health care quality assurance, 2019)
Purpose Risk identification plays a key role identifying patient safety risks. As previous research on risk identification practices, as applied to patient safety, and its association with safety culture is limited, the purpose of this paper is to evaluate current practice to address gaps and potential room for improvement. Design/methodology/approach The authors carry out interview-based questionnaires in one UK hospital to investigate real-world risk identification practices with eight healthcare staff, including managers, nurses and a medical consultant. Considering various aspects from both risk identification and safety culture practices, the authors investigate how these two are interrelated. Findings The interview-based questionnaires were helpful for evaluating current risk identification practices. While gaining significant insights into risk identification practices, such as experiences using current tools and methods, mainly retrospective ones, results also explicitly showed its link with the safety culture and highlighted the limitation in measuring the relationship. Originality/value The interviews addressed valuable challenges affecting success in the risk identification process, including limitations in safety culture practice, training, balancing financial and safety concerns, and integrating risk information from different tools and methods.